Pharmacokinetics and safety of recently approved drugs used to treat methicillin-resistant Staphylococcus aureus infections in infants, children and adults. Issue 3 (May 2014) - Gostelow, Martyn; Gonzalez, Daniel; Smith, P Brian; Cohen-Wolkowiez, Michael
<x xml:space="preserve">Abstract</x> Methicillin-resistant Staphylococcus aureus (MRSA) remains a significant cause of morbidity in hospitalized infants. Over the past 15 years, several drugs have been approved for the treatment of S. aureus infections in adults (linezolid, quinupristin/dalfopristin, daptomycin, telavancin, tigecycline and ceftaroline). The use of the majority of these drugs has extended into the treatment of MRSA infections in infants, frequently with minimal safety or dosing information. Only linezolid is approved for use in infants, and pharmacokinetic data in infants are limited to linezolid and daptomycin. Pediatric trials are underway for ceftaroline, telavancin, and daptomycin; however, none of these studies includes infants. Here, we review current pharmacokinetic, safety and efficacy data of these drugs with a specific focus in infants.